(untitled) (Ameghiniana, 2013)
The whole paper deals with the detailed description and illustration of the following bivalve species: Solemya (Janeia) ? sp., Grammatodon (Cosmetodon) sp., Modiolus ? sp., Myalinidae ? gen. et sp. indet., Leptodesma (Leiopteria) d. dutoiti (Harrington), Merismopteria sp., Euchondria aff. sabattinii González, Pectinacea gen. et sp .. indet., Elimatapermiana ? (King), Scbizodus sp., Netschajewia sp- nov. ?, d. Oriocrassatella sp., Edmondia d. prichardi Dickins and Sanguinolites sp. This bivalve fauna indicates a Lower Permian age, at least for the fossiliferous bed "D" of the Del Salto Formation, and thus, it is the second record of Permian rnarine bivalves from the Precordillera of Western Argentina. The bivalve assemblage also shows clase similarities with other faunas of Sakmarian- Artinskian age from Australia, India and Brazil.